2008
DOI: 10.1112/blms/bdm103
|View full text |Cite
|
Sign up to set email alerts
|

A problem of Hirst on continued fractions with sequences of partial quotients

Abstract: Let B denote an infinite sequence of positive integers b1 < b2 < . . ., and let τ denote the exponent of convergence of the series ∞ n=1 1/bn; that is, τ = inf{s 0 :1] : an(x) ∈ B(n 1) and an(x) → ∞ as n → ∞}. K. E. Hirst [Proc. Amer. Math. Soc. 38 (1973) 221-227] proved the inequality dimH E(B) τ /2 and conjectured (see ibid., p. 225 and [T. W. Cusick, Quart. J. Math. Oxford (2) 41 (1990) p. 278]) that equality holds. In this paper, we give a positive answer to this conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…In [16], Wang and the second author confirmed Hirst's conjecture without any assumption on Λ, that is,…”
supporting
confidence: 56%
“…In [16], Wang and the second author confirmed Hirst's conjecture without any assumption on Λ, that is,…”
supporting
confidence: 56%
“…In [1], Cusick proved Hirst's conjecture under some density assumption on B, he showed that if there exist constants c, q and r depending only on B such that r < τq and, for all real p q, the sequence B has at least cn τp−r members in every interval [(n − 1) p , n p ], then dim H E(B) = τ (B) 2 . In [7], we gave a positive answer to Hirst's conjecture without any assumption on B, that is…”
Section: Introductionmentioning
confidence: 91%
“…The Hausdorff dimension of this set was well studied by Bugeaud [5,7] and Bugeaud and Moreira [8] by also using the tools of continued fractions. For more dimensional results relating the partial quotients, see [9,10,13,16,17,19,22,23,25,26,34,35,37] and references therein.…”
Section: The Jarník-besicovitch Set Revisitedmentioning
confidence: 99%